2004
DOI: 10.1017/s003382220003589x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of 14C in the Terrestrial Environment in the Vicinity of Two European Nuclear Power Plants

Abstract: ABSTRACT. Radiocarbon is produced in all types of nuclear reactors. Most of the 14 C released into the environment is in the form of gaseous emissions. Recent data on the 14 C concentration found in terrestrial samples taken in the vicinity of nuclear power plants in Romania and Lithuania are presented. We found increased 14 C levels in the surroundings of both power plants. At the Romanian power plant Cernavoda, we found excess levels of 14 C in grass within a distance of about 1000 m, the highest 14 C specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 4 publications
3
22
0
Order By: Relevance
“…The mean measurement uncertainty is 2.5%. In terms of reference levels, these activity values are of the same order of magnitude as data published elsewhere: for instance, 259 Bq kg ÿ1 C in 1992 in milk, grain, leaf and root vegetables (Otlet et al, 1997), 259 Bq kg ÿ1 C in 1991 in tree rings in the United Kingdom (Isogai et al, 2002), 250 Bq kg ÿ1 C in 1998 in tree rings in Ireland (McGee et al, 2004) and 243 Bq kg ÿ1 C in 2000 in grass, tree leaves and mosses in Sweden (Magnusson et al, 2004). The above data agree with the results obtained from our study (Fig.…”
Section: Decline In 14 C Specific Activitysupporting
confidence: 59%
See 1 more Smart Citation
“…The mean measurement uncertainty is 2.5%. In terms of reference levels, these activity values are of the same order of magnitude as data published elsewhere: for instance, 259 Bq kg ÿ1 C in 1992 in milk, grain, leaf and root vegetables (Otlet et al, 1997), 259 Bq kg ÿ1 C in 1991 in tree rings in the United Kingdom (Isogai et al, 2002), 250 Bq kg ÿ1 C in 1998 in tree rings in Ireland (McGee et al, 2004) and 243 Bq kg ÿ1 C in 2000 in grass, tree leaves and mosses in Sweden (Magnusson et al, 2004). The above data agree with the results obtained from our study (Fig.…”
Section: Decline In 14 C Specific Activitysupporting
confidence: 59%
“…of the order of 60 Bq kg ÿ1 C in 1999 close to the site and values of up to 700 Bq kg ÿ1 C were measured between 1982 and 1984 around the same site (McCartney et al, 1988). Magnusson et al (2004) had specific activity measurements that showed levels close to 300 Bq kg ÿ1 C in terrestrial vegetation sampled in 2003 around two nuclear power plants in Romania and Lithuania. Furze samples measured in 1997e1999 in the area around the La Hague reprocessing plant in France had specific activity values above 580 Bq kg ÿ1 C (Fontugne et al, 2004).…”
Section: Ckg -1 C (Annual Mean)mentioning
confidence: 99%
“…14 CO 2 values 50-300‰ over background have been measured within 2 km of two German BWR reactors (Levin et al, 1988) and plant material around the Ignalina, Lithuania RBMK reactor is elevated by up to 20 000‰, with typical values 250‰ above background (Magnusson et al, 2004). In order to screen for such local enrichments we used the HYSPLIT back-trajectory model (Draxler and Rolph, 2003), obtaining back-trajectories for each sampling location and time (Fig.…”
Section: Co 2 Resultsmentioning
confidence: 99%
“…Most of the 14 C released into the environment by incinerators and BWRs is in the form of gaseous emissions (Magnusson et al, 2004) mainly via the stack gas, with CO 2 as the main carrier of 14 C. This radiocarbon or "hot source" released into the atmosphere is then available to enter plant carbon pools through photosynthesis or leads to an increase in the local 14 C concentration. Previous studies have reported high radiocarbon concentrations (97-184 pMC) in vegetation in areas more than 100 km distant from a nuclear power plant (Mikhajlov et al, 2004) and 14 CO 2 values 190-6000‰ over background in oak leaves sampled near two hazardous waste incinerators .…”
Section: "Hot Sources"mentioning
confidence: 99%